Multi Perception Analysis of Medan City Residents Against the River Environment - Indriyani Rachman; Ira Rumiris Hutagalung; Toru Matsumoto (Universitas Diponegoro, 2021)
Deli Medan River is one of the rivers used as a mode of transportation in the 1980s. The shift in water transportation to land causes the Deli Medan River not to get attention and tend to be ignored. This study aims to describe the perception of the people of Medan City on the Deli River Medan while at the same time looking for a correlation between each variable. This study involved 365 respondents divided from various urban villages in the Medan City area (136 men and 232 girls). The selected respondents are aged 9-60 years with a vulnerable elementary school to a college education. Spearman correlation analysis is used to see the relationship between variables. The results of the study inform that there is no relationship between pollution and siltation that occurs in the Deli River Medan, different results are shown between the changing of river transportation modes to land caused by river silting, the level of education and awareness in disposing of waste, as well as pollution that occurs and industries that dispose of waste. Wastewater in the Medan Deli River body (Sig. <0.05). Furthermore, the Deli Medan River has been polluting by waste and wastewater.